Long-term Follow-up of Observation-Only Management of Nontuberculous Mycobacterial Lymphadenitis. (October 2016) - Haimi-Cohen, Yishai; Markus-Eidlitz, Tal; Amir, Jacob; Zeharia, Avraham
A total of 21 children with clinically and microbiologically proven craniofacial nontuberculous mycobacterial lymphadenitis managed by observation only at a tertiary medical center in 1993-2005 were evaluated for scar parameters at least 2 years after diagnosis. Parents completed a satisfaction questionnaire. Median follow-up time from presentation was 6.8 years (range = 2.3-16.9 years). In all, 18 patients showed scar formation, for a total of 26 scars; 21 scars (81%) had a maximal length of ≤3 cm. Vascularity was normal in 20 scars (77%), and pigmentation was normal in 18 (69%); 21 scars (81%) had a normal to only mildly uneven surface. Although 8 parents (44%) reported that the presence of the scar disturbed them, all responders but one (94%) expressed overall contentment of observation only as a conceivable management alternative. In conclusion, an observation-only approach to craniofacial nontuberculous mycobacterial lymphadenitis is associated with an acceptable outcome and may be an alternative to patients who wish to avoid surgery.